Hak Memperoleh Pekerjaan Penyandang Disabilitas Dalam Proses Penerimaan Pegawai di Pemerintah Daerah - Julitia, Fina; Rumawi, Rumawi (Kertha Patrika, 2024)
The purpose of this study was to determine the right to obtain decent work for Persons with Disabilities carried out in the employee recruitment process at the Jember Regency Government. And to find out whether the process of recruiting employees with disabilities is in accordance with Law No. 8 of 2016. This study uses a qualitative approach, with the type of empirical research/ Field Research. Data collection techniques use observation, interviews and documentation. Data analysis techniques use purposive and snowball. Data validity with triangulation techniques (combined). The results of this study are that the employee recruitment process in Jember Regency has been carried out based on procedures and provisions from the central government, but this is still not in accordance with the field. That there are still several groups of people with disabilities who cannot work in the government realm. The Jember Regency Government is trying to fulfill the rights of people with disabilities by providing a quota of 2% for people with disabilities. Regarding the accommodation facilities provided by the government are inadequate and do not support the existence of employees with disabilities. The employee recruitment process at the Jember Regency Government has been carried out based on article 45 of Law No.  8 of 2016. However, the number of quotas received has not yet fully met the quota set by law.